Norwegian fairy tales - Strindberg, Gert (Bombay : Somaiya Publications, 1969)
Six Norwegian fairy tales whose characters are folk heroes of that country: Noekk, Nisse, Draug, Hulders, forest and mountain trolls
Keywords: Fairy tales -- Norway; Fairy tales; Folklore -- Norway